Impact of reactive surfaces on the abiotic reaction between nitrite and ferrous iron and associated nitrogen and oxygen isotope dynamics - Visser, Anna-Neva; Wankel, Scott D.; Niklaus, Pascal A.; Byrne, James M.; Kappler, Andreas; Lehmann, Moritz F. (Biogeosciences, 2020)
Anaerobic nitrate-dependent Fe(II) oxidation (NDFeO) is widespread in various aquatic environments and plays a major role in iron and nitrogen redox dynamics. However, evidence for truly enzymatic, autotrophic NDFeO remains limited, with alternative explanations involving the coupling of heterotrophic denitrification with the abiotic oxidation of structurally bound or aqueous Fe(II) by reactive intermediate nitrogen (N) species (chemodenitrification). The extent to which chemodenitrification is caused (or enhanced) by ex vivo surface catalytic effects has not been directly tested to date. To determine whether the presence of either an Fe(II)-bearing mineral or dead biomass (DB) catalyses chemodenitrification, two different sets of anoxic batch experiments were conducted: 2 mM Fe(II) was added to a low-phosphate medium, resulting in the precipitation of vivianite (Fe3(PO4)2), to which 2 mM nitrite () was later added, with or without an autoclaved cell suspension ( cells mL−1) of Shewanella oneidensis MR-1. Concentrations of nitrite (), nitrous oxide (N2O), and iron (Fe2+, Fetot) were monitored over time in both set-ups to assess the impact of Fe(II) minerals and/or DB as catalysts of chemodenitrification. In addition, the natural-abundance isotope ratios of and N2O (δ15N and δ18O) were analysed to constrain the associated isotope effects. Up to 90 % of the Fe(II) was oxidized in the presence of DB, whereas only ∼65 % of the Fe(II) was oxidized under mineral-only conditions, suggesting an overall lower reactivity of the mineral-only set-up. Similarly, the average reduction rate in the mineral-only experiments (0.004±0.003 mmol L−1 d−1) was much lower than in the experiments with both mineral and DB (0.053±0.013 mmol L−1 d−1), as was N2O production (204.02±60.29 nmol L−1 d−1). The N2O yield per mole reduced was higher in the mineral-only set-ups (4 %) than in the experiments with DB (1 %), suggesting the catalysis-dependent differential formation of NO. N- isotope ratio measurements indicated a clear difference between both experimental conditions: in contrast to the marked 15N isotope enrichment during active reduction ( ‰) observed in the presence of DB, loss in the mineral-only experiments exhibited only a small N isotope effect (<+1 ‰). The -O isotope effect was very low in both set-ups ( <1 ‰), which was most likely due to substantial O isotope exchange with ambient water. Moreover, under low-turnover conditions (i.e. in the mineral-only experiments as well as initially in experiments with DB), the observed isotope systematics suggest, transiently, a small inverse isotope effect (i.e. decreasing δ15N and δ18O with decreasing concentrations), which was possibly related to transitory surface complexation mechanisms. Site preference (SP) of the 15N isotopes in the linear N2O molecule for both set-ups ranged between 0 ‰ and 14 ‰, which was notably lower than the values previously reported for chemodenitrification. Our results imply that chemodenitrification is dependent on the available reactive surfaces and that the (rather than the N2O) isotope signatures may be useful for distinguishing between chemodenitrification catalysed by minerals, chemodenitrification catalysed by dead microbial biomass, and possibly true enzymatic NDFeO.<br